Indigenous religion and cultural performance in the new Maya world - Cook, Garrett W., 1947-; Offit, Thomas A., 1968-; Taube, Rhonda (Albuquerque [N.M.] : University of New Mexico Press, 2013)
"Based on more than thirty years of ethnographic fieldwork in Highland Guatemala, this study of Maya diviners, shamans, ritual dancers, and religious brotherhoods describes the radical changes in traditional Maya religious practice wrought by economic globalization and political turmoil"--Front jkt. flap.
Includes bibliographical references (p. 175-188) and index.
Description based on print version record.
Keywords: Mayas -- Guatemala -- Momostenango -- Religion; Mayas -- Guatemala -- Momostenango -- Rites and ceremonies; Mayas -- Guatemala -- Momostenango -- Social life and customs; Festivals -- Guatemala -- Momostenango; Shamanism -- Guatemala -- Momostenango; Cofradías (Latin America) -- Guatemala -- Momostenango; Momostenango (Guatemala) -- Religious life and customs; Momostenango (Guatemala) -- Social life and customs; RELIGION / Ethnic & Tribal; Electronic books